Factors Associated with Dyslipidemia in Adults Assisted by the Family Health Strategy in a Slum in Northeast Brazil - Melo, Silvia Pereira da Silva de Carvalho; Cesse, Eduarda Ângela Pessoa; Cruz, Rachel de Sá Barreto Luna Callou; Barreto, Maria Nelly Sobreira de Carvalho; Lira, Pedro Israel Cabral de; Rissin, Anete; Filho, Malaquias Batista (O Mundo da Saúde, 2023)
Among the factors associated with dyslipidemia, sociodemographic characteristics stand out, such as education and income and, from this perspective, less economically favored populations, such as those living in slums, are more likely to be affected by chronic non-communicable diseases when compared higher income populations. Therefore, considering the scarcity of studies related to the prevalence of dyslipidemia and its associated factors in inhabitants of slum areas, the objective of this study was to analyze the factors associated with dyslipidemia in adults assisted by the Family Health Strategy (FHS), living in slum areas, in Recife, Pernambuco. This is a cross-sectional, secondary-based study. Possible associations of dyslipidemia (isolated hypercholesterolemia or isolated hypertriglyceridemia) with demographic, socioeconomic and behavioral variables, body composition, and morbidities were analyzed using Poisson Regression, considering p<0.05. Of the 491 adults, 46.2% had dyslipidemia, which was higher in men compared to women (PR=1.70; 95%CI:1.41-2.03), with a progressive increase from the age of 30 and stabilizing around the 40-year-old range. Prevalence was higher among those who were insufficiently active (PR=1.21; 95%CI:1.01-1.45), with greatly increased waist circumference (PR=1.78; 95%CI:1.36-2.34), and with increased blood pressure (PR=1.35; 95%CI:1.11- 1.63). It is necessary to reinforce health promotion activities within the scope of the FHS for the investigated population, as well as to encourage the practice of physical activity in health academies, in addition to disseminating information regarding the fight against factors associated with dyslipidemia.